Editorial - Robles Olivos, Rafael (2021)
Technology is playing a key role in the global challenge what the pandemic caused by COVID-19 means. Societies, using remarkable resilience, embraced digital tools for continuity of their activities and, to the extent possible, achieved positive results in productive, business, educational, social spheres, among others.